2008
DOI: 10.1111/j.1747-7379.2007.00113.x
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and Well-Being: Perceptions of Refugees in Western Australia

Abstract: This paper reports the apparent paradox of high levels of discrimination experienced by humanitarian migrants to Australia, in the labor market and everyday life, yet simultaneous reporting of positive well‐being. How can people feel discriminated against, yet still be relatively satisfied with life? The study draws on quantitative and qualitative data from a study of 150 refugees from the former Yugoslavia, the Middle East, and Africa. Possible reasons for the level of well‐being are explored, including “rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(87 citation statements)
references
References 51 publications
3
78
0
Order By: Relevance
“…Unemployment can be an equally impactful experience that, if left unresolved, is likely to negatively influence settlement, health, and wellbeing (Abdelkerim & Grace, 2012;Blustein, 2008;Fozdar & Torezani, 2008;Paul & Moser, 2009;Taylor, 2004). Based on the International Labour Organization's standard definition, the category 'unemployed' is comprised of those individuals who are without paid work, available for work and seeking work.…”
Section: Unemployment and Settlement Among Refugees In Australiamentioning
confidence: 99%
“…Unemployment can be an equally impactful experience that, if left unresolved, is likely to negatively influence settlement, health, and wellbeing (Abdelkerim & Grace, 2012;Blustein, 2008;Fozdar & Torezani, 2008;Paul & Moser, 2009;Taylor, 2004). Based on the International Labour Organization's standard definition, the category 'unemployed' is comprised of those individuals who are without paid work, available for work and seeking work.…”
Section: Unemployment and Settlement Among Refugees In Australiamentioning
confidence: 99%
“…This is because there is a combination of political and economic forms of discrimination falling under the umbrella terminology "official ethnic discrimination" (Sorens, 2010). This is either due to the interest in labor discrimination being also detected in everyday life (Widner and Chicoine, 2011;Fozdar and Torezani, 2008) or to the discovery of means of circumventing it . Furthermore, the study of "gender discrimination" reveals discriminatory practices such as selective abortion and negligence in the healthcare of female children (Attané, 2009).…”
Section: La Revista Española De Investigacionesmentioning
confidence: 99%
“…These occur within the broader Australian community that consistently votes for politicians who stand for immigration control, and within under-resourced social and health systems that fail to apprehend and address complex refugee needs. Fozdar and Torezani (2008) found that despite various obstacles related to niche employment, low incomes, and discrimination, refugees in Western Australia did not report significant dissatisfaction with life (76.7% reported satisfaction). The authors attributed these results to mitigating factors such as culturally conditioned politeness, personality, social support, and the belief that despite experiences of discrimination, Australians are basically good people.…”
Section: Health and Painmentioning
confidence: 99%